Introduction to Dissection - Lawrence Wineski (Association of American Medical Colleges, 2006)
Abstract Many medical students do not enroll in undergraduate dissection-based anatomy courses during their premed education. As a result, they are not familiar with dissection instruments and the mechanics of dissection, and are poorly prepared for medical anatomy courses. This web-based module is designed to help overcome those deficits. It serves as an introduction to dissection in a human gross anatomy course for first-year medical students. It can be used either as a component of a structured classroom session, or, independently by individual students. The content is presented in a series of video clips arranged in two sections, each containing multiple chapters. The program is menu-driven, allowing for a viewing of the entire content in sequence, or elected chapters in any order. Students at Morehouse School of Medicine independently use this module before beginning dissection and report (informally) that they have a better understanding of what they are shopping for when they purchase their dissecting instruments after viewing the program. Both faculty and students report (informally) that students are more comfortable and confident while conducting their first dissection after viewing the program. Faculty believe the first dissection lab proceeds more efficiently since they implemented the use of this resource.